PROSES DAN KESAN KEMASUKAN BRITISH KE SINGAPURA 1819: CATATAN ABDULLAH ABDUL KADIR MUNSYI DALAM HIKAYAT ABDULLAH - Nordin, Mardiana (SEJARAH: Journal of the Department of History, 2017)
Hikayat Abdullah is a work in Malay literature written by Abdullah bin Abdul Kadir Munsyi. Unlike other works written before the 20th century that tend to be biases towards royal and aristocratic societies, Hikayat Abdullah takes a different attitude. Abdullah seems to write an auto-biography specifically about his life experiences from childhood to adult and his involvement in the lives of British officers. One subject caught his interest, that is the policies and methods of administration of colonial officers who were close to him such as William Farquhar and Thomas Stamford Raffles. Therefore, he ventured to write on the episode of British arrival in Singapore in 1819 with precision and much details. Undoubtedly, the arrival of the British in Singapore during that year is a very important historical event. Abdullah details his writing over the previous year and extends the story until a few years later. Thus, the study of these episodes through Hikayat Abdullah could provide an new understanding of the period.